Isothermal crystallization kinetics in bulk of olefin-based multiblock copolymers - Urciuoli, Gaia; Ruiz de Ballesteros, Odda; Femina, Giuseppe; Auriemma, Finizia (Frontiers in Soft Matter, 2022)
Isothermal crystallization kinetics of ethylene/1-octene (C2/C8) multiblock copolymers synthesized by chain shuttling technology is investigated. The samples are a reactor blend of segmented chains characterized by alternating crystalline and amorphous blocks with C8 content of 0.5 and 20 mol% respectively and statistical distribution of block number/chain and block length. The analysis is carried out after complete removal of a fraction (5-12 wt%), namely consisting of C8-rich blocks, through Kumagawa extraction with boiling diethyl ether. The resultant diethyl ether-insoluble fractions have similar average content of C8 units (13-14 mol%) and of crystalline blocks (23-27 wt%) but different molecular mass (the number average molecular mass Mn is 60-70 kDa for the samples 1,2 and 38 and 21 kDa for the samples 3 and 4, respectively). An additional sample with Mn 93 kDa, but a greater average content of C8 units (15 mol%) and a smaller content of crystalline blocks (15 wt%) is also analyzed. The crystallization half time of the samples increases with increase of Mn and, for each sample, its logarithm increases linearly with a decrease of the undercooling by a factor of -0.155/°C, for the samples 1-4 and -0.031/°C, for the sample 5. Using the classic kinetic crystallization model by Lauritzen and Hoffman, values of energy barrier constant due to contributions from primary nucleation KN and crystal growth KG are extracted, where the KN contribution is esteemed to amount to 34% of the total barrier assuming regime II for the sample 5 and regime III (or I) for the samples 1-4, to 34% for the samples 5 and 67% for the samples 1-4, assuming regime II for all the samples. In all the cases, regardless of the assumed regimes, the KN values of the sample 5 are lower than those of the samples 1-4. As a final remark, the implications of crystallization kinetics on the solid-state morphology are also discussed, considering that transmission electron microscopy (TEM) images present a partially mesophase separated morphology for the samples 1,2, and 5 and a classic lamellar morphology for the samples 3 and 4.